Populism in The United States During Donald Trump's Government: The Failure to Understand Human Identity from The Perspective of Constructivism - Pulungan, Eska Dwipayana (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2023)
This research analyzes human impartiality towards the single rationality of human ethics or cosmopolitanism in accepting racial, cultural, ethnic, and religious differences that have existed since the earth was created. The impartiality of the single value of human ethics takes Donald Trump's administration as the case study. After being elected as US President, Donald Trump followed the voice of his voters in determining the policies, especially regarding immigrants. Immigrants assessed undermine the country's economy and damage the social order of the local community. It resulted in a national political map that rejects the single rationality of ethical value of humanity, known as populism. Qualitative research methods are used by conducting in-depth research based on existing literature studies, including books used explicitly for theory development, journals to develop data, and media reports to analyze world leaders' responses towards Donald Trump's policies. Constructivism employs to analyze the case. The result was the rejection of the values of cosmopolitanism because of the community's disappointment with the government that offered jobs to strangers, especially immigrants without adequate skills, so the local community felt that their rights were being taken away and sacrificed under the pretext of justice. This assumption arose because people assumed their economic resources and welfare, such as job vacancies and social assistance provided by the state, absolutely belonged to them. This rejection then advocated to become an anti-immigrant issue, an act of rejection of differences in social identity that considers immigrants to be damaging to the economy, social stability and causing political turmoil that offends human identity. Trump used these community anxieties to win the 2017 US elections by using the political slogan Make America Great Again.